Quality of cesarean section nursing care and its reflection up-on women’s satisfaction with labor experience - H. Abdelati, Inaam; Hashim M. Saadoon, Om; Roshdi Ahmed Mostafa, Amal (International Journal of Advanced Nursing Studies, 2019)
Â Women satisfaction is a crucial predictor for maintaining and monitoring the quality of health care and can inform service development and delivery.Aim: To evaluate the quality of cesarean nursing care at hospital of Mansura University, the outcomes of it preserve ad-vanceandsupportqualityof care and womensatisfaction. By using a descriptive design the study conducted at obstetrics and gynecology department in Mansoura university hospital. On a total of 200women had undergoingelective cesarean section operation. Data collection by, structured interviewed questionnaire, observationchecklist and satisfactionassessment scale. Results; Findings indicated that most of studied women had received a complete care during intraoperative & immediate post-operative 92.5% & 95.0% respectively. Meanwhile, 80.0% & 62.5% of them didn't received health education and emotional support also , the higher percentage of studied women were satisfied with general environment, cleanliness, communication and physical care 75.0%, 75.0%, 65.0% and 58.0% respectively. While, 60.0% of them were dissatisfied with continuity of care. Regarding involving in decision making, all of studied sample100% were dissatisfied. Finally there was a positive association of quality of CS nursing care with the level of women's satisfaction with (p=<0.05) .Conclusion: The current study indicated that, there are several factors that affected on women's satisfaction. higher percentages of them were satisfied with general environment, cleanliness, communication and physical care and dissatisfied with psychological care, continuity of care and involvement in decision making. There was a highly statistically associationof womenâ€™s satisfaction with CS nursing care offered. Recommendation: Woman satisfaction is an imperative health care outcome its assessment is recommended tobe a part of hospital quality ofcare monitoring and improvement programs.Â Â